Powerful decomposition of complex traits in a diploid model - Johan Hallin (Nature Portfolio, 2016)
Dissecting the architecture of complex trait is challenging. Here, Hallin, Märtens et al. devises Phased Outbred Lines (POLs) in order to accurately decompose growth trait variation in diploid yeast across different environments.